Use the substitution method to solve the system of equations:
![\begin{gathered} x+y=18 \\ x=4+y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fqj3886nhyd03iotlwpw7ey1gre6i5tvym.png)
Since x is already isolated on the second equation, replace x with the expression for x in the first equation:
![\begin{gathered} x+y=18 \\ \Rightarrow(4+y)+y=18 \\ \Rightarrow4+2y=18 \\ \Rightarrow2y=18-4 \\ \Rightarrow2y=14 \\ \Rightarrow y=(14)/(2) \\ \therefore y=7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sjmpj2ye6061s76cablzrs1m6fx70osbku.png)
Substitute y=7 into the expression for x:
![\begin{gathered} x=4+y \\ \Rightarrow x=4+7 \\ \therefore x=11 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hp7jjsxvofg2c889yirxcllbu9lw6wn6u4.png)
Therefore, the solution for this system of equations, is:
![\begin{gathered} x=11 \\ y=7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/381p68lca5b1d54pyavhzzph3slsjqpxp3.png)